Career Preference in Teenagers: Social and Psychological Factors - Sh., Jumaev A. (Researchparks Publishing, 2023)
The pedagogy and psychology of emotional relations regarding human creativity, love, and friendship feelings, as well as the social activity of the individual as a factor in guiding young people to the profession, are examined in this article. The analysis is based on the scholars and thinkers of the East.